Main chemical constituents and pharmacological activities of Dimorphandra spp. - W. A. Silva; I. L. Soares; K. C. Mousinho; T. G. Araújo; G. M. Menezes; I. B. M. F. Alencar; G. S. Procopio; K. M. R. Araújo; R. B. Vasconcelos; R. B. V. Marinho; T. M. Wanderley; J. C. Costa; et al. (Brazilian Journal of Biology)
Abstract In the pharmaceutical industry, the fruits of the fava d'anta are used to extract quercetin and rutin, which are the basis for the production of medicines that work to treat varicose veins, hemorrhoids, circulatory system disorders and a variety of other conditions. The aim of this article is to carry out a comprehensive review of the chemical constitution and pharmacology of fava d'anta. This is an integrative review using the following databases: Embase, SciElo, LILACS, CAPES Periodicals and Medline, with the search expression “Dimorphandra gardneriana” OR “Dimorphandra mollis”. Studies were selected without any restrictions on language or time of publication, in order to conduct the most comprehensive search possible. A total of 278 articles were identified, of which 72 were viewed on Embase, 31 on Scielo, 19 on LILACS, 114 on CAPES and 42 on Medline. After reviewing the titles, abstracts and removing duplicates, 13 articles were obtained for full text analysis. The studies analyzed showed various pharmacological activities of the compounds extracted from the D. mollis and D. gardneriana species, including antioxidant, anti-inflammatory, neuroprotective, antiviral and lipid metabolism modulating properties. Thus, the presence of the flavonoids rutin and quercetin reinforces the potential of these species for therapeutic applications.